“The Biggest Small Town in America”: Cross-generational Patterns of Monophthongization in the Suburban South - Marc-Philippe Brunet (Anglophonia)
The phonology of the Southern states of the USA (Southern American English) is a well-documented phenomenon that has witnessed considerable change in the last century. Recently, many Southern states in the Sun Belt have been facing rapid urban growth along with a large influx of inhabitants from the rest of the country, leading to a change of the geographical environment as well as dwindling of prototypical features of Southern phonology in large urban areas. This paper seeks to explore the interactions and effects of urban growth and development on the vernacular phonology of the South. We will be looking at how residents and speakers adapt to the change of their locale by analyzing the residents’ realization of a key linguistic variable, the diphthong /aɪ/, regarded as a prototypical feature of Southern speech laden with social as well as symbolic meaning. This investigation was conducted in the theoretical and methodological framework of the PAC Programme (Phonology of Contemporary English: usage, varieties and structure) and within the LVTI Project (Language, Urban Life, Work, Identity), based on recent sociolinguistic fieldwork data obtained in Middle Tennessee. The results show that varying degrees of Southern speech can index a sense of rootedness and attachment to a perceived vanishing American South.